The coach-athlete relationship under capitalist constraint - Comyn, N. (First international symposium sciences and practices in swimming, 2006)
Individuals are now subjectively internalising a capitalist market model, which has major consequences on social bonds. New constraints apply to individuals. They have implications on the relationship between the coach and the athlete. This relationship is a specific social bond based on transference. This clinical and psychoanalytic study is aimed at analysing the consequences of the changes in the relationship and in the coach's approach, in competitive swimming. The first results of the study will be available soon.